Analysis of The Basis of The Creative Economy in The Development Strategy of Economic Innovation - Agus Rohmat Hidayat; Nur Alifah (Asian Journal of Social and Humanities, 2022)
Change occurs quickly and is full of vulnerabilities, such as the current COVID-19 situation, which is very difficult for supply chain managers, even though it currently has a very high level of normalcy. Consumer trends change very quickly and are difficult to predict. With the aim of a creative economy-based innovation development strategy, this study aims to identify the variables that influence the implementation and competitiveness of the innovative industries to be developed. It is important to note that the advertising process is not only about providing information, availability of goods, money and progress, but also has the advantage of providing information, quality map knowledge and applying valuable walking skills. The Strengths, Opportunities, Aspirations, and Outcomes (SOAR) survey and site survey were used to determine the optional process. A strategy that takes into account all the attractive quality points acquired. Therefore, in preparing object forms (translation exercises and communication activities), the potentials and challenges must be carefully weighed to achieve inclusive benefits in each implementation. The results of the SOAR study produced five alternative approaches. The most significant added value is the examination of the importance of possible resource accessibility with a value of 15,862, followed by second to fifth, access to rapid market changes (14,840), the establishment of associations (14,646), standardization and economy. Objects (14,123) and the development of productivity standards for competitiveness (12,288). An imaginative approach to business development should consider resource potential and quick response to advertising requests, along with three other components.